Clinical Perspective of Antimicrobial Resistance in Bacteria - Zhu Y; Huang WE; Yang Q (Infection and Drug Resistance, 2022)
Ying Zhu,1,2 Wei E Huang,3 Qiwen Yang1 1Department of Clinical Laboratory, State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2Graduate School, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 3Department of Engineering Science, University of Oxford, Oxford, OX1 3PJ, UKCorrespondence: Qiwen Yang; Wei E Huang, Email yangqiwen81@vip.163.com; wei.huang@eng.ox.ac.ukAbstract: Antimicrobial resistance (AMR) has become a global clinical problem in recent years. With the discovery of antibiotics, infections were not a deadly problem for clinicians as they used to be. However, worldwide AMR comes with the overuse/misuse of antibiotics and the spread of resistance is deteriorated by a multitude of mobile genetic elements and relevant resistant genes. This review provides an overview of the current situation, mechanism, epidemiology, detection methods and clinical treatment for antimicrobial resistant genes in clinical important bacteria including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), penicillin-resistant Streptococcus pneumoniae (PRSP), extended-spectrum β-lactamase-producing Enterobacteriaceae, acquired AmpC β-lactamase-producing Enterobacteriaceae, carbapenemase-producing Enterobacteriaceae (CPE), multidrug-resistant (MDR) Acinetobacter baumannii and Pseudomonas aeruginosa.Keywords: antimicrobial resistant, genes, antibiotic resistance mechanisms, epidemiology, detection methods